Pengaruh Resiliensi Dukungan Sosial, Self Confidence (Kepercayaan Diri) dan Perilaku Belajar Terhadap Prestasi Akademik Mahasiswa UPPJB-UT Makassar (Studi Pada Mahasiswa Pendas Pokjar Pinrang) - Muh. Ali; Muh. Alwi; Subirman Musa; Basmi Basmi; Burhan Burhan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study aims (i) to determine the effect of resilience of social support on student academic achievement at UPPJB-UT Makassar Study of Pendas Pokjar Pinrang Students; (ii) to determine the effect of self-confidence on student academic achievement at UPPJB-UT Makassar Study on Pendas Pokjar Pinrang Students; (iii) knowing the effect of learning behavior on student academic achievement at UPPJB-UT Makassar Studies on Pendas Pokjar Pinrang Students; and (iv) knowing the effect of social support resilience, self-confidence and learning behavior simultaneously on student academic achievement at UPPJB-UT Makassar Studies on Pendas Pokjar Pinrang Students. The research method uses a quantitative approach, and its type is correlational causality research. The technique of collecting data through a questionnaire. The population is UPPJB-UT Makassar students who study on Pendas Pokjar Pinrang students, totaling 667 people. The sampling technique used was random sampling in order to obtain 199 people. The data analysis technique used is descriptive analysis, path analysis requirements test and hypothesis testing. The results showed that the resilience of social support had a significant effect on the academic achievement of students at UPPJB-UT Makassar in the Study of Pendas Pokjar Pinrang Students; self-confidence (self-confidence) has a significant effect on student academic achievement at UPPJB-UT Makassar Studies on Pendas Pokjar Pinrang Students; Learning behavior has a significant effect on student academic achievement at UPPJB-UT Makassar Studies on Pendas Pokjar Pinrang Students; The resilience of social support, self-confidence and learning behavior simultaneously affects the academic achievement of students at UPPJB-UT Makassar Studies on Pendas Pokjar Pinrang Students.